Adaptive manet OLSR routing protocol for optimal route selection in high dynamic network - Al-Kharasani, Nori Mohammed Abdulkarem (2020)
Vehicular ad hoc networks (VANETs) are able to supply scalable and costefficient solutions for wide range of VANETs applications. The concept of multi-hop vehicle-to-vehicle wireless communications is essential for developing routing protocols. However, due to the rapid topology changes and frequent network disconnections, designing an efficient Multi-hop routing protocol for VANET environments is a very challenging problem. This is because of the vehicles mobility and road obstacles, which cause link failure frequent inefficiency in traditional mobile ad hoc routing protocols. Thus, the information that a vehicle collects using HELLO-Interval messages from its neighbours are not up to date to maintain the routes. When vehicles node cannot maintain routes successfully, the rapidly link failure limits the efficiency of routing. It introduce more control topology packets in the network to establishes new routes which lead to additional routing overhead and end to end delay. Therefore, Ad-hoc routing protocols need to address the problem of configuration adaptation and route selection mechanism to be suitable for VANETs. In this context, a major concern in designing an efficient routing protocol in VANETs lies on their configurations and route selection mechanisms. The promising applications of VANETs target little delay, overhead, stability and scalability network. For these reasons, optimizing routing configuration parameters, the cluster-based Quality of Service (QoS) and cross-layer parameters are an effective technique and widely accepted to improve routing performance. The main objective is to optimize utilization of the available network information in order to enable a balanced trade-off between the routing efficiency and VANETs constraints. In This thesis, three specific problems that impact VANETs routing efficiency are studied. The first objective to optimizing routing configuration parameter in different urban scenarios. The new framework model is introduced in order to provide a robust and reliable communication in VANETs, where the balance between the time needed to maintain the discovered routes and QoS requirements is necessary. The routing efficiency and roads constraints trade-off with adjustable soft communication is explored by tuning routing configuration parameters. The statistical framework based on QoS requirements is introduced for optimal solutions. The second objective considers improving route selection in dynamic network. The standard link reachability metric and the willingness of node cam not guarantee the stability of route. The absent of mobility metrics in route selection scheme leads to reduce the quality of route selection in VANET. The trusted communication range constraint takes into consideration to reduce the impact of dynamic mobility on routing efficiency, and path stability. A suitable algorithm called Link Stability Aware selection Multi Points Relay (LSA-MPR) is introduced, which find a route that satisfies constraints on multiple objectives for selecting the next hop as a relay node designed especially for VANETs, it finds a route that satisfies the constraints on multiple objectives based on Received Signal Strength Indicator (RSSI) and Signal to Interference-Noise Rate (SINR). The third objective considers reducing control topology overhead as well as improving the scalability of network. To provide the necessary robustness, a new Cluster-based Adoptive Cooperative Algorithm (CACA) for VANET is introduced to improve the scalability of the network and reduce control overhead. A number of factors are chosen to improve relay vehicle selection mechanism; The vehicle’s relative mobility, vehicle weighted, link reachability, and bandwidth metrics. These are considered to reduce link failure, routing overhead and enhance packet delivery ratios. The proposed Quality of Path QoP metric is incorporated into the modified relay selection algorithm, which improves the efficiency of relay selection mechanism to find optimal path with high link quality. The extensive simulation is performed to evaluate the proposed contributions, which have been presented with respect to urban network scenarios in order to evaluate the performance of the proposed contributions compared to various existing approaches. The comparison-based simulation of both default and modified routing protocols is carried out under certain performance parameters; Packet Delivery Ratio (PDR), Average End-to-End Delay (AE2ED), Normalized Routing Load (NRL), Average number of MPR, and Stability. The simulation results show that the BOLSR-PSO, LSA-MPR, and CACA significantly improve routing efficiency routing efficiency in VANET networks. The aim of this improvements are not only to maintained Packet Delivery Ratio, stability and scalability, but also to reduce the network overhead, and average delay.